2022
DOI: 10.3390/su142113877
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of an Energy Community Based on PV and Electric Storage Systems in a Small Mountain Locality of South Italy: A Case Study

Abstract: The ecological transition at the centre of the United Nations 2030 Agenda and the relevant EU policies are increasingly becoming an emerging issue in the political choices of most countries. It is an important challenge to ensure sustainable development and overcome the issue of energy supply. Italy produces 35% of its electricity consumption, a too low percentage that obligates the nation to purchase abroad to cover the overall needs. Energy communities can represent an interesting and viable option for busin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In their study, Minuto and Lanzini [42] included a simulation of an energy community with 100 households and a 100 kWp photovoltaic system, and six scenarios were developed to explore how profits could be shared among various members. Cirone et al [43] tested various energy community configurations by incorporating photovoltaic generators and electric batteries to optimize self-consumption for heat pump systems, for a REC located in a small town in Southern Italy. Viti et al [44] compared the performance of an energy community with a configuration where customers act as single self-consumers and found that energy communities are able to accelerate renewable energy sources deployment, resulting in higher overall self-consumption rates.…”
Section: Methodsmentioning
confidence: 99%
“…In their study, Minuto and Lanzini [42] included a simulation of an energy community with 100 households and a 100 kWp photovoltaic system, and six scenarios were developed to explore how profits could be shared among various members. Cirone et al [43] tested various energy community configurations by incorporating photovoltaic generators and electric batteries to optimize self-consumption for heat pump systems, for a REC located in a small town in Southern Italy. Viti et al [44] compared the performance of an energy community with a configuration where customers act as single self-consumers and found that energy communities are able to accelerate renewable energy sources deployment, resulting in higher overall self-consumption rates.…”
Section: Methodsmentioning
confidence: 99%
“…According to Mohammed [57], the geographic and climatic characteristics of Saudi Arabia allow it to depend on renewable energy sources and consider them financially desirable, so the government promotes initiatives that allow the diversification of its energy sources, which also explains the interest of researchers in addressing issues associated with the valuation of non-conventional renewable energy generation projects, such as photovoltaic energy, with storage systems. In the case of Italy and Spain, the ecological transition raised in the United Nations Agenda 2030 and the policies defined by the European Union have become the central issue in the policy options of most countries and a challenge to ensure sustainable development and solve the problem of energy supply [58]. This motivates the study of issues related to power generation, such as photovoltaics integrated with storage systems to ensure supply.…”
Section: The Leading Countries and Institutionsmentioning
confidence: 99%
“…Different analyses in the literature show that the best economic configuration is not always the one that ensures the lowest environmental impact as is often the case for a range of energy systems. Cirone et al [104] show that when sizing PV and storage systems in an EC, the optimal emission savings and net present value may not correspond to the same system configuration, leading to the need to choose a specific priority when designing the system. Sudhoff et al [105] compare different operation strategies in a specific EC, showing that an optimisation of the economic benefits of its members does not reduce the annual peak load, while a strategy focused on a grid-friendly renewable EC achieves a peak power reduction of 23-55%.…”
Section: Economic Impactmentioning
confidence: 99%